Crosstalk Apoptosis-Autofagi pada Kanker Serviks: Peran BAX, BCL-2, dan Cleaved Caspase-3 - Diah Komala Sari; Mgs Irsan Saleh; Subandrate Subandrate; Shaum Shiyan (Jurnal Biomedika dan Kesehatan, 2026)
Cervical cancer remains a major cause of cancer-related morbidity and mortality among women worldwide. In addition to persistent human papillomavirus (HPV) infection, dysregulation of cell survival and cell death mechanisms contributes to cervical cancer development and progression. Apoptosis and autophagy are two important biological processes involved in regulating cancer cell survival and death; however, the interaction between these processes remains complex and context-dependent. This review aimed to examine the crosstalk between apoptosis and autophagy in cervical cancer, with a particular focus on the roles of BAX, BCL-2, and cleaved Caspase-3. A narrative literature review was conducted using PubMed to identify publications related to apoptosis–autophagy crosstalk in cervical cancer, with particular attention to studies discussing BAX, BCL-2, cleaved Caspase-3, and selected autophagy-related regulators published between 2020 and 2025. Articles were selected based on relevance to the review topic and were synthesized descriptively to provide an overview of current evidence. The reviewed studies indicated that increased apoptotic activity was frequently associated with BAX upregulation, BCL-2 downregulation, and activation of cleaved Caspase-3. In contrast, autophagy exhibited a context-dependent role and functioned either as a mechanism of cancer cell death or as a protective process that promotes cancer cell survival. The interaction between BCL-2 and Beclin1, together with the PI3K/Akt/mTOR signaling pathway, emerged as important components of apoptosis–autophagy crosstalk. The conclusions was the balance between apoptosis and autophagy appears to influence cervical cancer cell responses to therapeutic interventions. BAX, BCL-2, and cleaved Caspase-3 may provide useful molecular information for future investigations of cervical cancer biology and therapeutic responses